The Project Training on Strengthening the Profile of Pancasila Students in Mathematics Learning at SMK Assalafiyyah Slema - Nuryadi*, Nuryadi; Khuzaini, Nanang (Universitas Lancang Kuning, 2024)
The Pancasila student profile strengthening project is an effort to encourage the achievement of the Pancasila student profile by using a new paradigm through project-based learning. Therefore, it is very important that schools can implement and run projects to strengthen the profile of Pancasila students. However, SMK Assalafiyyah Sleman has not implemented a project to strengthen the profile of Pancasila students. Therefore, the purpose of this service is to provide training and knowledge about the Pancasila student profile strengthening Project as well as the steps and flows of making the Pancasila student profile strengthening Project module at SMK Assalafiyyah Sleman. The training participants were all teachers at SMK Assalafiyyah Sleman as many as 14 teachers face-to-face using an approach of active participation, coordination and socialization, and independence. The results of Community Service (PKM) show that the achievement of the success indicators that have been set, namely ≥75% of teachers understand related to the project of strengthening the profile of Pancasila students. Therefore, Community Service (PKM) has achieved the success indicators that have been set and achieved the goal of making teachers at SMK Assalafiyyah Sleman know and understand related to the project of strengthening the profile of Pancasila students. In addition, the results of the research analysis above show that with proper assistance and policy making that favors all aspects involved in the world of education in Indonesia will greatly help the programs in the independent curriculum, one of which is the Pancasila student profile strengthening project program. In addition, collaboration can be an option for schools and teachers personally to better understand the programs in the independent curriculum in order to apply them in school learning